Coeloglossum viride Var. Bracteatum Extract Attenuates MPTP-Induced Neurotoxicity in vivo by Restoring BDNF-TrkB and FGF2-Akt Signaling Axis and Inhibiting RIP1-Driven Inflammation - Lang, Xiu-Yuan; Hu, Yang; Bai, Jin-Peng; Wang, Jun; Qin, Xiao-Yan; Lan, Rongfeng (Frontiers in Pharmacology, 2022)
The tuber of Coeloglossum viride var. bracteatum is a Tibetan medicine that has been used for generations as a tonic for Yang and Qi, tranquilizing, to enhance intelligence and to promote longevity. We have previously characterized the constituents of Coeloglossum viride var. bracteatum extract (CE) and investigated its anti-Alzheimer’s disease (AD) effect in mice models. However, the exact role of CE in Parkinson’s disease (PD), especially the neurotrophic and inflammatory pathways regulated by CE, remains unknown. In this study, we investigated the anti-PD effects of CE in an MPTP-induced acute mouse model and its underlying mechanisms, focusing on BDNF, FGF2 and their mediated signaling pathways and RIP1-driven inflammatory signaling axis. Pole test and traction test were performed for behavioral analysis. RT-PCR, IHC and Western blotting were performed to assay the mRNA, tissues, and protein, respectively. We found that CE improved dyskinesia in MPTP-intoxicated mice, which was confirmed by the pole test and traction test. Also, oxidative stress and astrocyte activation and inflammation were alleviated. MPTP-intoxication disrupted the levels of BDNF, FGF2 and their mediated signaling pathways, triggered elevation of pro-inflammatory factors such as TNF-α, IL-1β, and IL-6, and activated RIP1-driven inflammatory axis. However, CE restored the levels of BDNF, FGF2 and TrkB/Akt signaling pathways while inhibiting the RIP1-driven inflammatory signaling axis, thereby inhibiting apoptosis, preventing loss of nigrostriatal neurons, and maintaining cellular homeostasis. Thus, CE is a promising agent for the treatment of PD.